Reduction in gastrointestinal bleeding by development and implementation of a protocol for stress ulcer prophylaxis: a before-after study. Issue 1 (December 2015) - Ikemura, Mai; Nakasako, Shinji; Seo, Ryutaro; Atsumi, Takahiro; Ariyoshi, Koichi; Hashida, Tohru
Abstract Background The implementation of a protocol has been associated with improvements in the processes of care in clinical settings. Although stress ulcer prophylaxis is recommended for critically ill patients at high risk, there is currently no consensus on its use. Therefore, we herein developed a protocol for stress ulcer prophylaxis, and evaluated therapeutic outcomes in a before-after study. Methods The protocol was developed by considering the effectiveness, disadvantages (including adverse events) and cost of each agent based on previous findings. Patients who were admitted to the 8-bed emergency intensive care unit (ICU) of our hospital for more than 24 h during the year before and after implementation of the study were eligible. Each investigation item was evaluated retrospectively. Results There were 211 and 238 study patients before and after implementation of the protocol, respectively. The baseline characteristics of patients on/during ICU admission were similar in the two groups. The proportion of medicated patients was 79.6 % before and 84.5 % after protocol implementation. Before implementation of the protocol, 4.3 % of patients developed clinically important gastrointestinal bleeding, and this incidence decreased significantly to 0.8 % after its implementation (P  = 0.019). The frequency at which medication was discontinued due to adverse events was slightly lower after implementation of the protocol. No significant differences were observed in the costs of stress ulcer prophylactic agents or mortality in the ICU. Conclusions The results of the present study indicated that the development and implementation of a protocol for stress ulcer prophylaxis, for which there are currently no criteria, improved a main outcome, clinically important gastrointestinal bleeding.